To evaluate the expression cd - d + 2e + 10, we substitute the given values for c, d, and e.
cd - d + 2e + 10 = (5)(2) - 2 + 2(9) + 10
= 10 - 2 + 18 + 10
= 28
Therefore, when c=5, d=2, and e=9, the value of the expression is 28.
Evaluate cd - d + 2e + 10, when c=5, d=2, and e=9.
3 answers
It's wrong
Apologies for the mistake in my previous response.
To evaluate the expression cd - d + 2e + 10, we substitute the given values for c, d, and e.
cd - d + 2e + 10 = (5)(2) - 2 + 2(9) + 10
= 10 - 2 + 18 + 10
= 28
Therefore, when c=5, d=2, and e=9, the value of the expression is 28.
To evaluate the expression cd - d + 2e + 10, we substitute the given values for c, d, and e.
cd - d + 2e + 10 = (5)(2) - 2 + 2(9) + 10
= 10 - 2 + 18 + 10
= 28
Therefore, when c=5, d=2, and e=9, the value of the expression is 28.